Hydrogen evolution behavior of nickel coated TiO2 - Döner, Ali; Uzal, Hasan; Bayrakçeken, Hüseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Nickel modified titanium dioxide nanotubes (TiO2-NTs/Ni) and TiO2-NTs electrodes are investigated for hydrogen evolution reaction (HER). To obtain large surface area, TiO2-NTs are prepared by using anodization method at a constant voltage of 60 V for various anodization times (30 min, 1 h and 2 h). Small amount of Ni is successfully deposited over TiO2-NTs via electrodeposition method. Hydrogen evolution activities of TiO2-NTs/Ni and TiO2-NTs are investigated in 1 M KOH solution at room temperature. Characterizations of prepared nano structured electrodes are analyzed with scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and cyclic voltammetry (CV) and electrochemical-activities are determined through cathodic current-potential curves and electrochemical impedance spectroscopy (EIS). Hydrogen volumes produced from prepared electrodes are also measured under constant voltage of 3 V for 30 min. Obtained results showed that hydrogen evolution activity increased with the modification of TiO2-NTs by nickel. High current density at specific overpotentials, hydrogen volume and small polarization resistance are obtained on TiO2-NTs/Ni. High stability and durability are also obtained on this electrode. So, TiO2-NTs/Ni as an electrocatalyst is suggested to use in water electrolysis systems. (c) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Water splitting; Hydrogen evolution reaction; Titanium dioxide nano-tube; Stability